Tannin Test on Celery Leaves (Apium graveolens L.) Using UV-Vis Spectrophotometry Method as an Active Ingredient in Hand Sanitizer - Adelina, Dina; Adlin, Irman Ansari; S, Agustina Dyah; Junita, Rusnia (Jurnal Teknologi, 2025)
This study looks into whether celery leaves (Apium graveolens L.) could be used as a source of tannins for making hand sanitizer. This study attempts to find a natural antibacterial agent that can be used instead of hand sanitizers, which are in high demand during the COVID-19 pandemic. The goal was to measure the amount of tannins in celery leaves and see how well they work in hand sanitizers. We used the UV-Vis spectrophotometry approach to find out how much tannin there was, using quercetin as a benchmark. We used maceration with 96% ethanol to get the tannins out, and then we distilled them. The results showed that there was a strong linear association between absorbance and tannin concentration. The average tannin content was 0.1397 mg/g. Then, the celery leaf extract was added to hand sanitizer gels. Successful organoleptic testing showed that the composition was physically stable and had antibacterial properties. This study shows how to use local plant materials, such celery leaves, to make hand sanitizers that are good for the environment and work well. This is a better option than chemical-based solutions. The results show that this method could work on other plants with similar traits.